Application of 2D and 3D Electrical Resistivity Tomography (ERT) in Predicting Soil Erodibility in Oredide Village, Auchi in Etsako West LGA of Edo State, Southern Nigeria - D.A. Babaiwa; M.O. Ikponmwen (Journal of Applied Sciences and Environmental Management)
Geoelectrical investigation of the subsurface employing 2D and 3D electrical resistivity tomography (ERT) was carried out to ascertain the soil erodibility in Oredide village, Auchi, Etsako LGA of Edo State with a view to averting imminent colossal damage to land resource and its accompanying infrastructure. A total of 10 traverses, 200 m long each were occupied in grid format using the Dipole - Dipole electrode configuration. 2D results indicate topsoil with resistivity value range of 309 to 40130 Ωm within the depth range of 0 to 5 m. The second layer corresponds to sandy, lateritic sand, sand and sandstone having resistivity values ranging from 2186 to 60350Ωm to a depth of 10.0 m. The third layer has resistivity values indicating lateritic sand, sand and sandstone layer with resistivity values ranging from 2186 to 60350 Ωm within the depth of 20 m. The fourth layer connotes lateritic sand, sand and sandstone to a depth of 30m. The fifth horizon has resistivity values in the range of 585.2 to 35732.4 Ωm which is representative of sand and sandstone.The maximum depth imaged was 47.7 m. The inverted 2-D resistivity structure shows high resistivity distribution near-surface >1000 Ωm, which are indications of vulnerabilities to erosion in the study area with depth of scouring being 15 m. 3D horizontal depth slice show four layers with depths: 0 – 3.5 m, 3.5– 7.52 m, 7.52 – 12.2 m and 12.2 – 17.5 m having corresponding resistivity values that vary from 465 – 285939 Ωm across each layer respectively. Resistivity values vary from 358 – 217741 Ωm and a 3D depth of 15.4 m was imaged; correlating with the 2D results.